Cultural Space Protection for “Waving Dance” by Tujia People in Youyang from the Perspective of Cultural Identity - Fu, Lanmei; Rattachaiwong, Nataporn; Jin, Qianqiu (Journal of Dhamma for Life, 2025)
We explored Waving Dance in the southeast Chongqing by applying the Theory of Cultural Space from the perspective of cultural identity. It is of great significance for protection and development in the cultural space of Waving Dance, as well as for rejuvenation and revitalization of the cultural circle of Wuling Corridor through route exploration. The Tujia People in the southeast of Chongqing forms one of the most important parts of the Tujia People living in Wuling Mountains. Due to their different geography, living environment and historical circumstance, they are different from the Tujia People in Guizhou, Hunan and Hubei. As time changes, the culture of Waving Dance has kept evolving in a Procrustean way to adapt to the external environment. Such a passive inheritance mode has impacted the entire cultural space with Waving Dance at its core, and thus hindered the cultural rescue, protection and development. The cultural space of Waving Dance was explored and the dilemma against cultural development was analyzed herein regarding the Theory of Cultural Identity. The significance among the Waving Dance, the ethnic identity and the cultural confidence of Tujia People were analyzed objectively from the “people-oriented” idea to “overall promotion”, as well as from the ontological protection under cultural ecology to the cultural transmission and future prospects of Waving Dance.